The performance of plastic solar collector as part of two contours solar unit - Selikhov, Yu. A.; Kotsarenko, V. A.; Klemes, J. J.; Kapustenko, P. O. (My University, 2018)
The use of solar collectors made of polymeric materials allows absorbing solar radiation most fully and reduce the material consumption of the solar installations. The results of experiments with flat plate solar collector with absorber made of special grade polyethylene are presented. The obtained correlations for dependences of the coefficient of efficiency and the specific heat flux from the flow rate of the heat carrier, the heat carrier temperature at the exit from the solar collector, the operating time of the solar installation during the daylight at different coolant flow rates can be used for reliable design of solar heating systems and for integration of plastic solar panels into heating systems in industry and communal sector.
Keywords: solar collectors; polymeric materials; coefficient of efficiency; specific heat flux; heat carrier